2021
DOI: 10.14744/tjtes.2021.70728
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Annona muricata (graviola) in experimental spinal cord injury: biochemical and histopathological analysis

Abstract: BACKGROUND: Annona muricata (AM) (graviola) is a plant that grows in tropical regions and is thought to be good for many diseases by local people. Unfortunately, there is no acceptable medical treatment for spinal cord injury (SCI) yet. In our study, we investigated the neuropeotective effects of AM leaf extract on SCI in an experimental rat model. METHODS:A total of 40 Wistar albino rats were randomly divided into five equal groups (n=8). Group 1 was the control group in which only laminectomy was performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
4
0
2
Order By: Relevance
“…According to the literature, CoQ10 can modulate apoptosis (Doimo et al, ). Ostrowski and colleagues concluded that use of CoQ10 (10 mg/kg) immediately after trauma had protective effects against ischemic injury in experimental models of ischemia in the brain hemispheres and spinal cord (Erol et al, ; Kerimoğlu et al, ; Ostrowski, , ). In our results we concluded CoQ10 alone could have protective effects on hippocampal injury.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, CoQ10 can modulate apoptosis (Doimo et al, ). Ostrowski and colleagues concluded that use of CoQ10 (10 mg/kg) immediately after trauma had protective effects against ischemic injury in experimental models of ischemia in the brain hemispheres and spinal cord (Erol et al, ; Kerimoğlu et al, ; Ostrowski, , ). In our results we concluded CoQ10 alone could have protective effects on hippocampal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Güncel kılavuzların çoğu, akut SKY için rutin MP uygulamasını önermemektedir [18,19]. Bu nedenle, SKY için farklı terapötik ajanlar (baicalein, graviola, melatonin gibi) deneysel çalışmalarda araştırılmaya devam etmektedir [20][21][22].…”
Section: Discussionunclassified
“…Flavonoidlerin antiinflamatuar aktivitelerinde yer alan moleküler mekanizmaların siklooksijenaz-2, lipoksijenaz ve indüklenebilir NO sentaz gibi proinflamatuar enzimlerin inhibisyonu, NF-kB'nin inhibisyonu ve aktive edici protein-1 ve faz II antioksidan detoksifiye edici enzimlerin, mitojenle aktive olan protein kinazın, protein kinaz C'nin ve nükleer faktör-eritroid 2-ilişkili faktör 2'nin aktivasyonu olduğu öne sürülmüştür [19,20]. SKY' sı sonrası flavanoidlerin nöroprotektif özellikleri, miyelin akson kaybını, glial skar oluşumunu ve astrosit proliferasyonunu azaltarak gösterdiği belirtilmiştir.…”
Section: Discussionunclassified
“…It is suitable for many diseases (such as fever, malaria, diabetes, rheumatism, various cancers) by local people in tropical regions; branches, bark, leaves, seeds and root parts are processed through various processes [18]. AM is known to have anticarcinogenic, anticonvulsant, antiinflammatory, antioxidant, radioprotective (against gamma rays) and neuroprotective properties [20,[30][31][32]. However, there are limited studies on the radioprotective effect of AM in the literature [30,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Another important antioxidant enzyme, GPx, reduces lipid peroxides to hydroxyl lipids and waters by converting glutathione to glutathione disulphide [41]. There are studies in the literature on the antioxidant, antiinflammatory and neuroprotective effects of both crude extracts and phytochemical compounds of AM [30][31][32]. Moghadamtousi et al, examined the effects of AME on wound healing in an experimental injury model.…”
Section: Discussionmentioning
confidence: 99%